Aortic remodeling, reintervention, and survival after zone 0 arch repair with frozen elephant trunks for acute type A aortic dissection: Midterm resultsCentral MessagePerspective - Takuya Wada, MD; Hiroshi Yamamoto, MD, PhD; Daichi Takagi, MD, PhD; Takayuki Kadohama, MD, PhD; Gembu Yamaura, MD, PhD; Kentaro Kiryu, MD, PhD; Itaru Igarashi, MD (JTCVS Techniques)
Objectives: To investigate the midterm results after zone 0 arch repair with frozen elephant trunks for acute type A aortic dissection. Methods: Between October 2014 and April 2021, 196 patients underwent zone 0 arch repair with frozen elephant trunks for acute type A aortic dissection. The true lumen area, aortic lumen area, and false lumen status were assessed at four aortic levels, the proximal and distal descending thoracic aorta (level A and level B, respectively), celiac artery branching (level C), and terminal aorta (level D). Aortic remodeling (postoperative area as a percentage of the preoperative area) was classified into 3 groups, positive (true lumen area ≥120% with aortic lumen <120% or true lumen area ≥80% with aortic lumen <80%), minimal (80% ≤ true lumen area and aortic lumen area <120%), and negative remodeling (all other changes). Results: In-hospital mortality was 13 (6.6%) patients. The overall survival rate was 85.1% at 5 years. The freedom from distal aortic reintervention was 89.9% at 5 years. The prevalence of completely thrombosed or obliterated false lumen at 2 years was 96.8% at level A, 88.4% at level B, 47.2% at level C, and 27.6% at level D. The prevalence of positive aortic remodeling at 2 years was 84.7% at level A, 75.0% at level B, 29.2% at level C, and 16.7% at level D. Conclusions: Zone 0 arch repair with frozen elephant trunks for acute type A aortic dissection can avoid invasive aortic arch resection and facilitate aortic remodeling of the descending thoracic aorta. The FET effect on aortic remodeling is limited at the aortic level below the FET stent end.